Magnetic resonance imaging in degenerative ataxic disorders. Issue 1 (January 1994) - Ormerod, I E; Harding, A E; Miller, D H; Johnson, G; MacManus, D; du Boulay, E P; Kendall, B E; Moseley, I F; McDonald, W I
Abstract : MRI of the brain was performed in 53 patients with a variety of degenerative ataxias and related disorders and 96 control subjects. Atrophy of intracranial structures was not seen in patients with the pure type of hereditary spastic paraplegia, or in early cases of Friedreich's ataxia. In advanced Friedreich's ataxia there was atrophy of the vermis and medulla. The MRI features of early onset cerebellar ataxia with retained reflexes were variable, and suggest heterogeneity. In autosomal dominant cerebellar ataxias, most patients had cerebellar and brainstem atrophy, probably reflecting the pathological process of olivopontocerebellar atrophy; there was no clearly defined group with both clinical and imaging features of isolated cerebellar involvement. The MRI abnormalities in idiopathic late onset cerebellar ataxia were predominantly those of cerebellar and brainstem atrophy or pure cerebellar atrophy. The clinical and imaging features of brainstem abnormalities were discordant in several patients. Pure cerebellar atrophy was associated with slower progression of disability. Cerebral atrophy was common in the late onset ataxias. Cerebral white matter lesions, although usually few in number, were observed in significantly more patients than controls, particularly those aged over 50 years.